Nest boxes in planted and regrowth Forest Red‐gum (Eucalyptus tereticornis Sm.) ecosystems. (May 2015) - Smith, Geoffrey C.; Hogan, Luke D.; Franks, Alan; Franks, Stacey
Summary Nest boxes were deployed in planted and regrowth areas in association with a revegetation project to restore Forest Red‐gum (Eucalyptus tereticornis) ecosystems on abandoned former agricultural land. A year after revegetation began, 36 boxes were installed in each of the planted and regrowth areas in 2003, and these were monitored to 2013. Sixteen vertebrate species utilised boxes, which included breeding by four species and two species that were not detected by other survey methods. More boxes were used by fauna in the planting compared to regrowth in all but one audit. Significantly, more boxes were used by reptiles in regrowth than planting, but significantly more by birds in planting than regrowth. Nearly 90 per cent of boxes remained intact over the 10‐year period. While the study's capacity to attribute results to habitat types was limited, the results do add weight to the possibility that nest boxes made of good quality materials can provide valuable habitat for a wide range of species during the early recovery phase of reforestation projects.